Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Produktivitas pekerja Buruh di PT XYZ dengan metode PLS-SEM - Setiawan, Deni; Lahay, Idham Halid; Pratiwi, Monica (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Work productivity is an important factor in improving company performance, especially for labor workers whose performance is strongly influenced by the work environment and job satisfaction. This study aims to analyze the effect of the work environment and job satisfaction on worker productivity at PT XYZ. The research method used is a quantitative descriptive approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The variables used in this study include the work environment as variable X1, job satisfaction as variable X2, and work productivity as variable Y. The results show that the work environment has a positive and significant effect on work productivity with a path coefficient value of 0.579 and a P-value of 0.000. Job satisfaction also has a positive and significant effect on work productivity with a coefficient value of 0.338 and a P-value of 0.006. The R-square value of 0.750 indicates that these variables explain 75% of work productivity, while the remaining 25% is influenced by other variables outside this study.